Análisis financiero a la Cooperativa de Ahorro y Crédito Servidores Municipales de Loja Ltda. de la ciudad de Loja, periodo 2021-2022. - Sánchez Azuero, Junnior Antonio (2024)
The Curricular Integration Work entitled Financial Analysis of the Municipal Savings and Credit Cooperative Municipal servants de Loja Ltda. in the city of Loja, for the period 2021-2022 was developed with the purpose of understanding the economic-financial situation to contribute to the growth of the mentioned organization and in compliance with the set objectives. The methodology refers to the approach, type, and design of the research; scientific, mathematical, statistical, inductive, deductive, analytical, and synthetic methods were used, as well as observation, interview, and literature review techniques. Through vertical and horizontal analysis, the most relevant items were identified, with credit portfolios in assets and obligations to the public in liabilities increasing by 13.96% and 3.62% respectively in 2022, evidencing an increase in financial intermediation, as well as a 12.93% increase in equity due to contributions and profits obtained. Economically, income from generated interests and expenses from operations grew by 17.52% and 12.10% respectively in the year 2022, registering improved profitability. Similarly, the application of financial indicators carried out as indicated by the Superintendence of Popular and Solidarity Economy for cooperatives of segment 4; having a delinquency rate of 0.45% and 0.61% in each respective period, showing adequate levels and reflecting good portfolio recovery, in addition to not maintaining high unproductive assets. However, the most significant deficiencies for the institution are found in liquidity, with 12.97% and 7.06% respectively, indicating insufficient resources to meet short-term obligations, and in profitability, despite recording profits, inefficient management is evident. With all this information, the financial report was formulated, detailing the results regarding the financial and economic structure. In conclusion, the cooperative is not able to meet immediate obligations due to a low level of liquidity, in addition to reflecting unfavorable profitability despite having profits, this is a problem, as it affects the internal financial and economic health of the institution.